Pan-Am in Bid to Ease 'Jamming': 'Pan Fever' Blasts Off Sun. - Unknown (Daily Express)
Pan American Airways (Pan Am) has made a bid to smooth the flow of passenger through Piarco Airport for the hectic pre-Carnival season. Pan Am has arranged for two immigration officers to go to the United States to help expedite passenger - handling procedures. Additionally, Pan Trinbago's "Pan Fever '76" starts officially at Skinner Park, San Fernando with 27 steelbands taking part in the qualifying round of the competition.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Tourism -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago